In vitro fertilization in height - Vargas, Luis Alberto (2015)
Objective: To determine the feasibility of in vitro fertilization (IVF) procedures at 3330 meters above sea level (masl). Design: Prospective clinical study. Settings: Centro de Fertilidad y Ginecología del Sur (CFGS), Cusco, Peru city localized at 3330 masl. Participants: Couples with unexplained infertility, tubal obstruction, decreased ovarian reserve or Asherman syndrome. Interventions: Since 2005 we have performed IVF procedures in 12 couples: 8 by coventional IVF surrogacy. Main outcome measures: Implantation, and biochemical and clinical pregnancies rates. Results: In the conventional IVF and egg donation IVF groups the implantation rates were 6,9% and 9,1%, the biochemical pregnancy rates 37,5% and 33,3%, and the clinical pregnancy rates 12,5% and 33,3% respectively. Conclusions: It is possible to have successful IVF procedures at 3330 masl. The higd altitude could be a negative factor for embryo implantation.